Bare magnetic nanoparticles as fluorescence quenchers for detection of thrombin. Issue 12 (21st June 2015) - Yu, Jiemiao; Yang, Liangrong; Liang, Xiangfeng; Dong, Tingting; Liu, Huizhou
<x xml:space="preserve">Abstract</x> Bare magnetic nanoparticles as fluorescence quenchers and an aptamer as an affinity ligand were used to detect thrombin, and this is a simple and sensitive assay.